Antara Linguistik dan Hukum Islam - Hizbia Qurani; Solehodin Solehodin; Kahfi Ya Kahfi (SUHUF, 2026)
The diversity of Qurʾanic qiraʾat has significant semantic and interpretive implications in the study of tafsir, particularly in verses related to gender ethics and legal norms concerning women. This study analyzes the reading variants qarna and qirna in Surat al-Ahzab (33): 33 and their influence on the divergent interpretations of Ibn ʿAtiyyah (d. 546 AH/1151 CE) and al-Qurtubiy (d. 671 AH/1273 CE). This research employs a qualitative-descriptive method based on library research, with al-Muharrar al-Wajiz by Ibn ʿAtiyyah and al-Jami' li-Ahkam al-Qurʾan by al-Qurtubiy serving as the primary sources. The findings show that Ibn ʿAtiyyah tends to prioritize the reading qirna, regarding it as stronger in terms of transmission and more eloquent linguistically. His interpretation emphasizes the ethics of composure, honor, and women’s dignity, while tending to limit the legal implications of the verse primarily to the Ahl al-Bait. By contrast, al-Qurtubiy adopts a more inclusive stance toward both readings and develops a more normative and protective interpretation, especially in relation to women’s presence in the public sphere and social morality. This difference is shaped not only by methodological choices, but also by scholarly networks, epistemological orientations, and the socio-political contexts surrounding the two exegetes. Ibn ʿAtiyyah, who lived in a relatively stable and linguistically oriented Andalusian milieu, produced a more selective and descriptive form of exegesis. Meanwhile, al-Qurtubiy, who lived in a more dynamic socio-political context and within a stronger juristic orientation, produced a broader, more argumentative, and more normative interpretation. This study argues that Qurʾanic tafsir is not merely a textual product, but also an intellectual process shaped by specific historical and social contexts.